Clival metastasis of hepatocellular carcinoma: a case report of a rare skull-base malignancy - Felbabić, Tomislav; Bošnjak, Roman; Urbančič, Jure; Bošnjak, Matic; Vozel, Domen (Frontiers in Oncology, 2026)
IntroductionHepatocellular carcinoma is the most common neoplasm of the liver. It metastasizes mainly to local lymph nodes, lungs, adrenal glands, vertebrae, pelvis, ribs and long bones. Metastasis to the clivus is extremely rare. Only a few cases have been described in the literature. Therefore, there is currently no clear consensus on the optimal treatment: biopsy only or maximum safe removal.Case reportWe present a 68-year-old lady who presented with dysfunction of the 6th and 12th cranial nerves. Imaging showed tumor formation in the clivus, most likely a metastasis. Further diagnostics revealed no clear primary tumor. The patient therefore underwent surgery for local decompression and simultaneous biopsy for pathohistologic examinations. These showed that the most likely metastasis was a hepatocellular carcinoma. Subsequent diagnostics revealed highly elevated alpha-feto protein levels and liver MR revealed a suspected multifocal hepatocellular carcinoma only after correlation with the pathohistologic findings. One month after surgery, the condition suddenly worsened due to severe local recurrence and hemorrhage. This was followed by palliative oncological treatment with whole head irradiation.ConclusionIn the case of a suspected clivus metastasis of unknown origin, it is reasonable to take tumor markers. This increases the likelihood of an appropriate diagnosis and avoids unnecessary and risky surgery. If all tests are inconclusive, a biopsy of the lesion is the diagnostic gold standard. The treatment of metastatic disease in the clivus (in our case a hepatocellular carcinoma) remains palliative.